On the Confined High-strength Concrete and Need of Future Research. (2017) - Antonius; Imran, Iswandi; Setiyawan, Prabowo
Abstract: Investigation about requirements of confining reinforcement on the structure of high-strength concrete has been progressed significantly since the last three decades. Research carried out intensively on high-strength concrete, produces a material which has a relatively brittle nature. Various parameters of the confining reinforcement design have been varied to obtain the optimal results regarding the behavior of high-strength concrete, especially for columns comprehensively. This paper discussed about the development roadmap of confined high-strength concrete research, includes constitutive equations of confined high-strength concrete developed by researchers. In this paper modified of analytical model for confined normal to high-strength concrete is also proposed. Results of this further discussion were associated with the need of the development research of confining reinforcement on high-strength concrete material adapted to the material properties and zones in Indonesia.